Reading Hebrews and James : a literary and theological commentary - Isaacs, Marie E. (Reading the New Testament series., 2002)
Reading Hebrews & James provides a clear path through the unique and often divisive Letter to the Hebrews and Letter of James. Isaacs's commentary on these two letters expertly considers questions of authorship and historical context while also making both Hebrews and James undeniably relevant for today's faith.